PELATIHAN PENYUSUNAN RENCANA BISNIS (BUSINESS PLAN) BAGI WIRAUSAHA MUDA DI DESA KUTUH, KECAMATAN KUTA SELATAN, KABUPATEN BADUNG - Fahmi Tanjung; Putu Ratna Windusara Putri; I Made Wisnu Wardana; I Made Sujana (Nusantara Hasana Journal, 2022)
This community service program aimed to improve the ability of young entrepreneurs to prepare systematic and applicable business plans in Kutuh Village, South Kuta District, Badung Regency. The main problems faced by young entrepreneurs include limited knowledge of business planning, market analysis, marketing strategies, financial management, and business proposal preparation. The program was implemented through socialization, training sessions, mentoring, group discussions, and practical business plan development activities. The participants consisted of 30 young entrepreneurs who either owned businesses or were in the process of starting new ventures. The results indicated significant improvements in participants’ understanding of business planning concepts, SWOT analysis, marketing strategies, and financial management. Furthermore, participants successfully developed simple business plan documents that could serve as practical guidelines for running and expanding their businesses. This program positively contributed to enhancing entrepreneurial capacity among young people in Kutuh Village and encouraged the establishment of more structured and sustainable business ventures.